1991
DOI: 10.1177/0022002791035002008
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Domestic and International Politics on the President's Use of Force

Abstract: Ostrom and Job (1986) found that domestic, political factors are more influential on the president's decision to use military force than characteristics of the international environment. These results pose a serious challenge to realists' assumptions regarding the motives of states and the separability of domestic and foreign policy. This article reexamines Ostrom and Job's arguments and introduces a new indicator, a measure of the severity of ongoing international crises, to provide a better assessment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
159
1
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(164 citation statements)
references
References 27 publications
2
159
1
2
Order By: Relevance
“…Some scholars have suggested that this dynamic should apply primarily to democratic leaders because of their dependence on public support for maintaining office and because of their inability to use more direct methods of dampening domestic dissent (Richards et al 1993, Downs & Rocke 1995, Gelpi 1997. Consistent with this expectation, several studies of American foreign policy indicate that presidents have been more likely to use military force when their approval ratings have been in decline (Ostrom & Job 1986, James & Oneal 1991, Fordham 1998. Other studies have indicated-contrary to the diversionary logic-that U.S. presidents have been more likely to use military force when economic conditions have been favorable (Lian & Oneal 1993, Meernik & Waterman 1996.…”
mentioning
confidence: 95%
“…Some scholars have suggested that this dynamic should apply primarily to democratic leaders because of their dependence on public support for maintaining office and because of their inability to use more direct methods of dampening domestic dissent (Richards et al 1993, Downs & Rocke 1995, Gelpi 1997. Consistent with this expectation, several studies of American foreign policy indicate that presidents have been more likely to use military force when their approval ratings have been in decline (Ostrom & Job 1986, James & Oneal 1991, Fordham 1998. Other studies have indicated-contrary to the diversionary logic-that U.S. presidents have been more likely to use military force when economic conditions have been favorable (Lian & Oneal 1993, Meernik & Waterman 1996.…”
mentioning
confidence: 95%
“…But many of these studies and their underlying empirics have been heavily criticized. The conclusions and suppositions they employ have elicited a host of efforts to replicate the findings by altering measures for key variables or repeating the analyses in different periods (e.g., James and Oneal 1991). The results of such efforts have been mixed at best and the United States is likely to be the exception rather than the norm, given its position of power.…”
Section: Diversionary Expectationsmentioning
confidence: 99%
“…Therefore, the final models excluded these control variables to focus on the substantive, clustering effect. 14 Klare, 1981;Pearson and Baumann, 1977;Yoon, 1997. 15 Brands, 1988;James and O'Neal, 1991. 16 See, for example, James Fearon, "Domestic Political Audiences and the Escalation of International Disputes," American Political Science Review, Vol.…”
Section: Approachmentioning
confidence: 99%